The Effect of Patterns of Space Circulation on the Understanding and Satisfaction of Visitors to the Museum of Makassar - Shiber, Nahridzah Mahjubuh; Rahman, Muhammad Haristo; Jusbaeni, Jusbaeni (Journal of Civil Engineering, 2025)
The Museum of Makassar, in its capacity as a representative space of urban history and culture, plays a pivotal role is fostering collective public awareness of city’s heritage. However, the undirected circulation structure of the exhibition space engenders a fragmented and unsystematic visitor experience. The objective of this research is to examine visitor circulation patterns in Museum of Makassar and formulate a spatial movement model that is able to integrate curatorial narratives more effectively. This research utilizes a qualitative approach, employing direct observation, spatial mapping and spatial configuration analysis to evaluate the relationship between the movement of visitors and their comprehension of exhibition content. The findings of this research are anticipated to contribute of the development of spatial planning strategies for museums that are more communicative, directed and inclusive, thereby supporting museum in their role as inclusive and immersive public learning spaces.